Organization of Islamic Cooperation (OIC) Humanitarian Diplomacy in Assisting Refugees During Pandemic - Rizki Dian Nursita; Putri Regina Ayu Wulansari; Esti Wahyu Ningtyas; Angelina Iskandar Saputri (Journal of Islamic World and Politics, 2023)
The pandemic that has occurred since the end of 2019 has become a scourge for the global people. The number of Internally Displaced Persons (IDPs), which reached 82 million people, has caused them to become the most vulnerable group during the pandemic. According to the latest UN Refugee Agency (UNHCR) report, over 116,000 COVID cases have been reported among the refugees. Organization of Islamic Cooperation (OIC), as the world's second-largest inter-governmental organization, should tackle this vulnerability, considering that one of the OIC’s Programme Actions programs is developing the Joint Islamic Humanitarian Action. This study used humanitarian diplomacy as the conceptual framework to explore the extent of diplomacy carried out by OIC in assisting IDPs and refugees during the pandemic. This research applied qualitative methods for data collection and analysis. This research found that, during the pandemic, OIC has carried out actions to address the issue of refugees, such as promoting international norms relating to refugees, initiating international discussions and forums related to the condition of refugees during the pandemic, and collaborating with other international organizations in monitoring refugee assistance during the pandemic. However, most OIC’s roles are limited to organizing or facilitating international forums rather than engaging in the affected area.